Black Colouration of the Knee Articular Cartilage after Spontaneously Recurrent Haemarthrosis. (12th May 2016) - Matsumoto, Kazu; Ishimaru, Daichi; Ogawa, Hiroyasu; Akiyama, Haruhiko
Abstract : Mild discolouration of the articular cartilage is known to gradually occur during aging. However, pathological tissue pigmentation is occasionally induced under several specific conditions. In the present case, we performed total knee replacement in a patient with recurrent haemarthrosis. However, during the operation, we observed severe black colouration of the knee articular cartilage, due to the deposition of hemosiderin and lipofuscin. To our knowledge, this is the first report of severe cartilage pigmentation, due to hemosiderin and lipofuscin deposition in articular cartilage.